2013
DOI: 10.1158/1078-0432.ccr-13-0341
|View full text |Cite
|
Sign up to set email alerts
|

ETS2 Mediated Tumor Suppressive Function and MET Oncogene Inhibition in Human Non–Small Cell Lung Cancer

Abstract: PURPOSE The ETS2 transcription factor is an evolutionarily conserved gene that is deregulated in cancer. We analyzed the transcriptome of lung adenocarcinomas and normal lung tissue by expression profiling and found that ETS2 was significantly down-regulated in adenocarcinomas. In this study, we probed the yet unknown functional role of ETS2 in lung cancer pathogenesis. EXPERIMENTAL DESIGN Lung adenocarcinomas (n=80) and normal lung tissues (n=30) were profiled using the Affymetrix Human Gene 1.0 ST platform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
241
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(246 citation statements)
references
References 43 publications
4
241
1
Order By: Relevance
“…RNA expression data revealed that the overall level of expression of ETS2 was unchanged in this tumor, although the levels of exons 7 and 8 were markedly reduced, suggesting that exon skipping occurs as a result of viral integration. ETS2 is a tumor suppressor gene (35), and previous reports have shown that truncated ETS family proteins may act in a dominant negative fashion (36). Our findings suggest that insertion of viral sequences into one of two copies could result in the loss of function of this gene.…”
Section: Hpv Integrations Are Associated With Somatic Alterations Of Keysupporting
confidence: 49%
“…RNA expression data revealed that the overall level of expression of ETS2 was unchanged in this tumor, although the levels of exons 7 and 8 were markedly reduced, suggesting that exon skipping occurs as a result of viral integration. ETS2 is a tumor suppressor gene (35), and previous reports have shown that truncated ETS family proteins may act in a dominant negative fashion (36). Our findings suggest that insertion of viral sequences into one of two copies could result in the loss of function of this gene.…”
Section: Hpv Integrations Are Associated With Somatic Alterations Of Keysupporting
confidence: 49%
“…The mRNA expression profile data of GSE43458 [12], including 80 lung cancer samples and 30 normal samples, was downloaded from the GEO (Gene Expression Omnibus) database in NCBI (National Center for Biotechnology Information) (http://www. ncbi.nlm.nih.gov/geo/) based on the platform of GPL6244 [HuGene-1_0-st] Affymetrix Human Gene 1.0 ST Array [transcript (gene) version].…”
Section: Methodsmentioning
confidence: 99%
“…Chan et al [11] used the GSE43458 microarrays to construct the molecular probes for lung cancer, while Kabbout et al [12] proved the suppression role of ETS2 in human non-small lung cancer cells by inhibiting of the MET proto-oncogene using the same profile data. In this study, we used the microarray analysis to screen the differentially expressed genes (DEGs) in lung cancer based on the mRNA microarray GSE43458 and SNP microarray GSE33355.…”
mentioning
confidence: 99%
“…The cells were stained with methyl violet prior to end of the incubation and the number of colonies was counted under a light microscope (Olympus Corporation, Tokyo, Japan). (11). Genes that were significantly differentially expressed in cells, with or without WWOX overexpression, were selected based on exhibiting P<0.05 and a 1.5-fold-change (FC).…”
Section: Cellmentioning
confidence: 99%